The Flare Irradiance Spectral Model‐Version 2 (FISM2). Issue 12 (2nd December 2020) - Chamberlin, P. C.; Eparvier, F. G.; Knoer, V.; Leise, H.; Pankratz, A.; Snow, M.; Templeman, B.; Thiemann, E. M. B.; Woodraska, D. L.; Woods, T. N.
Abstract: The Flare Irradiance Spectral Model (FISM) is an important tool for estimating solar variability for a myriad of space weather research studies and applications, and FISM Version 2 (FISM2) recently was released. FISM2 is an empirical model of the solar ultraviolet irradiance created to fill spectral and temporal gaps in the satellite observations. FISM2 estimates solar ultraviolet irradiance variations due to the solar cycle, solar rotations, and solar flares. The major improvement provided by FISM2 is that it is based on multiple new, more accurate instruments that have now captured almost a full solar cycle and thousands of flares, drastically improving the accuracy of the modeled FISM2 solar irradiance spectra. Specifically, these new instruments are the Solar Dynamics Observatory (SDO)/Extreme Ultraviolet Variability Experiment (EVE), Solar Radiation and Climate Experiment (SORCE)/X‐ray Photometer System (XPS), and SORCE/Solar Stellar Irradiance Comparison Experiment (SOLSTICE). FISM2 is also improved to 0.1‐nm spectral bins across the same 0‐ to 190‐nm spectral range and is already being used in research to estimate space weather changes due to solar irradiance variability in planetary thermospheres and ionospheres. Key Points: FISM2 accurately models spectral irradiance variations due to the solar cycle, solar rotation, and solar flares FISM2 fills temporal, from 1947 to present, and spectral, from 0–190 nm, gaps in the measurements of SORCE/XPS, SDO/EVE, and SORCE/SOLSTICE FISM2 is a much improved solar ultraviolet irradiance model over the first version released more than 15 years ago